Descriptive analysis of anthropometric and body composition characteristics in youth cycling performance - Burhaan Shodiq; Inosen Lingsir Maghribi; Muhamad Ihsan Hufadz; Azry Ayu Nabillah; Erny Amalia Lestari; Burhaan Shodiq; Inosen Lingsir Maghribi; Muhamad Ihsan Hufadz; Azry Ayu Nabillah; Erny Amalia Lestar (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2026)
Cycling performance is influenced by anthropometric characteristics and body composition that play a role in power production and motion efficiency. This study aims to describe the relationship of anthropometric characteristics and body composition with bicycle racing performance in adolescent mountain bike (MTB) athletes. The study used a descriptive quantitative design with a sample of three top-ranked athletes in the 2025 MTB criteria race in the 12-15 year age category in Lampung, Indonesia. Variables measured include completion time, final rating, height, weight, body mass index (BMI), body fat percentage, and muscle mass percentage. Anthropometric Data were measured using a stadiometer, body composition using bioelectrical impedance analysis (BIA), and racing performance was obtained from official competition records. Data analysis is done descriptively. The results showed that athletes with better performance tended to have a lower percentage of body fat and a higher percentage of muscle mass. Athletes with the fastest times had the most favorable body composition profiles, while BMI and general anthropometric measures did not show a consistent pattern of relationship with performance. Inferences of body composition, particularly low body fat and high muscle mass, are more related to cycling performance than to general anthropometric measures or BMI. However, these findings need to be interpreted carefully due to the very small sample size. Further studies are suggested involving larger samples and additional physiological variables.